(x^2)(e^x) - 2x(e^x) = 0
e^x x(x - 2) = 0
Therefore:
x = 0
x = 2
e^x can never be 0.
2007-08-23 07:25:34
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Factorize left hand side of the equation and write it as:
(e^x)*x(x - 2) = 0.
Now e^x can never be zero for any real finite value of x because e > 2. So either x = 0 or x - 2 = 0 ---> x = 2.
Therefore solutions are x = 0 or x = 2.
2007-08-23 14:33:37
·
answer #2
·
answered by quidwai 4
·
0⤊
0⤋
In factored form the equation is x*(e^x)*(x - 2) = 0. Therefore either x = 0 or x - 2 = 0, because e^x is never 0. Thus, x = 0 or x = 2.
2007-08-23 14:28:04
·
answer #3
·
answered by Tony 7
·
0⤊
0⤋
Try x = 2. It works for me. Also x = 0.
2007-08-23 14:26:03
·
answer #4
·
answered by morningfoxnorth 6
·
0⤊
0⤋
if you write it as
x²e^x = 2xe^x and divide by e^x (which you can do assuming it's not 0), you get
x² = 2x
x² - 2x = 0
x(x-2) = 0
x = 0 or x = 2.
in order for e^x to be 0 we'd need x = -â, which isn't a solution.
2007-08-23 14:28:15
·
answer #5
·
answered by Philo 7
·
0⤊
0⤋